Neighbourhoods for the city in Pacific Asia - Ho, Kong-Chong, 1955- (Asian cities (Amsterdam, Netherlands), 2020)
The largest cities in East Asia are the engines of their countries' economic growth, seats of national and regional political power, and repositories of the nation's culture and heritage. The economic changes impacting large cities interact with political forces along with social-cultural concerns, and in the process also impact the neighbourhoods of the city. My study looks at local collective action and city government responses and its impact on the community and the city. By adopting a multi-sited comparative approach in studying local action in five important cities (Bangkok, Hong Kong, Seoul, Singapore and Taipei) in Pacific Asia, the book enables comparisons across a number of key issues confronting the city: heritage (Bangkok and Taipei), community involved provisioning of amenities in a number of different contexts (Hong Kong, Seoul, Singapore), place making versus place marketing (Hong Kong). The collaborative efforts city governments establish with local communities becomes an important way to address the liveability of cities.